The prevalence of the defining features of primary ciliary dyskinesia within a cri du chat syndrome cohort. Issue 11 (20th September 2018) - Sanders, Catherine D.; Leigh, Margaret W.; Chao, Kay C.; Weck, Karen E.; King, Ian; Wolf, Whitney E.; Campbell, Dennis J.; Knowles, Michael R.; Zariwala, Maimoona A.; Shapiro, Adam J.
Abstract : Background: Primary ciliary dyskinesia (PCD) and cri du chat syndrome (CdCS) are distinct disorders that can co‐occur due to a common genetic locus on chromosome 5p. Chronic respiratory symptoms associated with PCD can occur in CdCS and are typically attributed to hypotonia, dysphagia, and aspiration. The prevalence of PCD among individuals with CdCS is not known. Methods: An online survey assessing common features of PCD was distributed to members of the 5P Minus Society, a cri du chat patient advocacy group. Respondents who met criteria for elevated risk of PCD (at least 3 symptoms or other features highly suggestive of PCD) were offered PCD genetic testing. Results: For the 123 respondents (median age 10.1 years with IQR 5.5‐17.3 years; from 33 U.S. states and 10 other countries) chronic respiratory symptoms associated with PCD were prevalent, including unexplained neonatal respiratory distress, year‐round nasal congestion beginning in infancy, and year‐round, wet cough beginning in infancy in 35%, 32%, and 20% of respondents, respectively. Fifteen respondents (12%) met criteria for elevated risk for PCD and completed genetic analysis; however, none were diagnostic for PCD. A PCD clinical center evaluated an additional subject with CdCS who met criteria for likely PCD and had negative genetics, but had diagnostic electron microscopy of the respiratory cilia (missing outer dynein arms). Conclusion: Clinicians should be aware of the genetic connection between CdCS and PCD. Non‐informative genetic testing does not rule out PCD. CdCS patients with chronic respiratory symptoms may benefit from referral to specialized PCD diagnostic centers.